The Olympus Scandal and Corporate Governance Reform: Can Japan Find a Middle Ground between the Board Monitoring Model and Management Model? - Aronson, Bruce E. (Zeitschrift für Japanisches Recht, 2013)
SUMMARY Since the 1990s global institutional investors have strongly advocated the widespread use of independent directors in accordance with the U.S.-derived board monitoring model. Japan may be the country that has displayed the greatest resistance to this prescription for reform. The fallout from the scandal over financial reporting at Olympus Corporation provides a new opportunity to reconsider both theoretical and practical issues related to Japanese corporate governance reform. This Article proposes that the deadlocked debate in Japan over director independence be expanded to produce more effective reform. The aim is to pay closer attention to current proposals and to the ongoing experimentation at a number of leading Japanese companies. Their goal is to develop a mixed governance system that seeks a “middle ground” between Japan’s traditional management board model and the monitoring model. Proposals should also consider means to spread such best practices more broadly among Japanese companies. Although current proposals and experimentation in Japan have the potential to achieve significant corporate governance reform, it is too early to judge whether the post-Olympus ferment will, in fact, lead to the incorporation of an effective management monitoring function into the traditional Japanese corporate structure. ZUSAMMENFASSUNG Global agierende institutionelle Investoren werben seit den 1990er Jahren mit Nachdruck für einen verstärken Einsatz von unabhängigen Mitgliedern in den Verwaltungs- bzw. Aufsichtsgremien von Unternehmen nach US-amerikanischem Vorbild. Japan ist vermutlich das Land, das sich diesem Ansinnen am nachhaltigsten widersetzt hat. Die Nachwirkungen des Rechnungslegungsskandals bei dem Unternehmen Olympus geben Anlass, erneut über theoretische und praktische Aspekte im Zusammenhang mit der Reform der Corporate Governance in Japan nachzudenken. Der Beitrag schlägt vor, die festgefahrene Diskussion über die Unabhängigkeit von Verwaltungsratsmitgliedern in Japan perspektivisch zu erweitern, um so eine effizientere Reform zu ermöglichen. Ziel ist, den aktuellen Vorschläge und organisatorischen Experimenten führender japanischer Unternehmen größere Aufmerksamkeit zu schenken. Diese versuchen einen Mittelweg zwischen Japans tradiertem Modell eines von Managern dominierten Verwaltungsrates und eines demgegenüber stärker von Aufsichtsaspekten geprägten zu finden. Entsprechende Vorschläge müssen zugleich der Problematik der Umsetzung bei den japanischen Unternehmen Rechnung tragen. Auch wenn die diskutierten Vorschläge und Experimente das Potential haben, zu einer bedeutenden Reform der Corporate Governance in Japan zu führen, ist es noch zu früh, um beurteilen zu können, ob es im Zuge der Unruhe nach dem Olympus-Skandal tatsächlich zur Integration einer effizienten Unternehmensüberwachung in die tradierte japanische Unternehmenskultur kommen wird. (Übersetzung durch die Redaktion)